Urban native and non-native bird species are functionally redundant in Santiago, Chile - Castro-Morales, S; Ray-Bobadilla, C (SPRINGER, 2026)
Urban expansion has profoundly transformed the composition and functional structure of bird communities, especially in cities where native and non-native species coexist. Nevertheless, little is known about how these species are distributed within functional trait space or what their coexistence implies for maintaining ecological functions. We evaluated the functional diversity of Santiago s urban avifauna, consisting of the 41 native and 5 non-native species that inhabit the city. We constructed a species x traits matrix based on seven functional attributes (i.e., mean adult body mass, diet, foraging method, foraging substrate, activity period, nesting substrate, and mean clutch size). Based on this matrix, we quantified the functional overlap between native and non-native birds and, complementarily, calculated four functional diversity indices: functional richness (FRic), divergence (FDiv), specialization (FSpe), and originality (FOri). 60% of non-native birds were embedded within the functional space defined by native ones, whereas only 7.3% of natives fell within the space occupied by non-natives. This asymmetry did not differ significantly from null expectations (P = 0.783), and the values of functional diversity indices between both groups were not statistically different either (all tests P > 0.203). Although native birds showed numerically higher values of functional richness, divergence, and specialization (FRic = 0.920; FDiv = 0.816; FSpe = 0.580, respectively) than non-native birds (FRic = 0.019; FDiv = 0.781; FSpe = 0.520), and non-native species exhibited higher functional originality (FOri = 0.415 vs. 0.275), these patterns did not translate into statistically significant differences (permutation test; P > 0.20 for all indices). Our findings indicate substantial functional redundancy between native and non-native birds, suggesting that the latter do not expand the urban trait space, with potential implications for the range of ecological functions sustained in cities.